Case series of dissociative identity disorder in teenagers: clinical features and treatment consideration - Zakaria, Rozanizam; Tengku Kamarulbahri, Tengku Mohd Saifuddin; Harun, Noorul Amilin; Hussin, Suria (Wolters Kluwer Medknow, 2023)
Dissociation is an unconscious defense mechanism that helps to protect oneself from trauma. It comes in various forms, such as dissociative identity, memory loss, and altered perception. Dissociative identity disorder (DID) is a serious psychological disturbance that can occur due to maladaptive dissociation patterns. However, it is not commonly identified in clinical practice. This case series presents three clinical cases of DID in adolescents with different predispositions. One case involved a male adolescent with autism spectrum disorder, while the other two cases involved female adolescents with depression and a history of sexual abuse. The report emphasizes the importance of screening for dissociative symptoms, proper diagnosis and treatment approaches, and the challenges in diagnosis and management. This information can help clinicians to improve their knowledge and skills in managing similar cases involving adolescents.